External Debt Problem in the European Union - I. A. Balyuk; M. A. Balyuk (Мир новой экономики, 2021)
The paper's relevance is substantiated by the fact that today a rapid growth of external debt of the most developed countries of the world (including European Union (EU) countries) is one of the most acute problems of the modern world economy and global finance. The paper aims to assess the degree of the external debt burden of various EU countries and evaluate the prospects of solving external debt problems in the EU. The article focuses on dynamics, composition, and specifics shaping the EU countries' external debt based on comparative, economic, statistical, and graphical analysis. Special attention we paid to the analysis of specifics of the EU countries' sovereign external debt composition connected with the acute problem of the rapid growth of public debt in general. The paper examines the ratio of public external and internal debt in various EU countries. It determines the EU particular countries where public external debt is shaping based on either cross-border or domestic model. The research results reveal a high degree of dependence of the EU economy on international debt finance. Gross external debt and sovereign external debt of the EU countries are still growing, and its distribution among various member states is very uneven. The structural imbalance of the EU countries' net external debt has also been revealed: the number of net borrowers is double that of net lenders. According to the basic external debt sustainability indicators, some EU countries are in a pretty tricky situation and entirely depend on the possibility of external debt refinancing.